Turning the International North-South Corridor into a ‘Digital Corridor’ - Hriday Ch. Sarma (Сравнительная политика, 2018)
At present, the INSTC is being widely discussed among policy makers and academia as on the ground progress is fast taking shape. The project has primarily remained an initiative of four major participating states – i.e. India, Iran, Azerbaijan and Russia – that are territorially located along the route of the corridor. Private businesses, whether local companies or MNCs, have not been very interested to jointly develop the project, mostly out of their concerns for assured returns on investments. The study builds a comprehensive case for the participating states to actively engage the private companies for developing the mega-connectivity project. The latter holds an advantage over advanced digital technologies in the global markets. Hence, public-private partnerships will bring about application of advanced digital technologies, like IoT, Blockchain technology, etc., which will efficiently serve the needs of different activities happening along the entire length of the corridor. This, in turn, will increase the overall strength and utility of the corridor, thereby ensuring its lasting success.